Formulation of nanocellulosic fibres and particle fillers and their mono and hybrid reinforced polymer composites - Webo, Wilson Wachuli (Vaal University of Technology, 2022)
This study aimed to focus on the state of knowledge and practice on natural fibres, extract cellulose, and subsequent formation of nanocellulosic fibres and particles from selected natural fibres. Moreover, both mono and hybrid composites were fabricated and modeled using ABAQUS software. After that, the formulation of the optimal mix ratio of both the fibres and the matrix for different mechanical applications was determined using the Minitab software version 2017. Sisal and rice husk were selected for this purpose due to their ease of availability. An experimental solution was used to extract cellulose, and, subsequently, nanofibres and nanoparticles were formed. These were then used to fabricate composites. The possibility of using new processing technology for modeling both sisal and rice husk nanocomposites in their mono and hybrid forms through the use of Finite Element Analysis (FEA) is a novel idea that has been explored in this study. Finite Element Analysis (FEA) using ABAQUS/CAE software version 2018 was used to develop novel models of mono and hybrid nanocomposites and to determine their mechanical properties of strength and stiffness. The finite element analysis method incorporates the effects of nonlinearities which are very common in composite fabrication. Furthermore, this study sought to formulate the optimal combination mix ratio of fibres and matrix for different mechanical applications using the Minitab software version 2017. A total of 198 finite element part models were created and analyzed. The Finite Element Analysis (FEA) models developed predicted correctly the flexural and tensile properties of the nanocellulosic composites that had been modelled. The experimental method was used to validate the FEA results. Moreover, analysis of variance (ANOVA) was performed for each property of the mono and hybrid composites in this study. The tensile and flexural properties of the mono and hybrid composites were found to gradually increase with an increase in fibre volume fraction up to a certain optimum point, beyond which they gradually began to reduce with more fibre additions. The analysis of variance of properties indicated that, for all the tensile and flexural properties under study, the F statistic > F critical, and the P-value < 0.05, implying that the tests were significant and there was a difference between the means of the groups. In the thermal analyses, the Thermogravimetric Analysis(TGA) graph exhibited three distinct sections: An initial flat section, then a section with a constant slope and finally a flat section. In the Dynamic Scanning Calorimetry (DSC) graphs, all the samples exhibited a glass transition temperature of between 50ºC and 75ºC. Furthermore, all the samples exhibited a melting temperature of between 350ºC and 400ºC. Overall, the hybrid nanocomposites had better tensile, flexural and thermal properties than the mono composites. Regarding the formulation of the optimal combination mix of the fibres and the matrix for use in different mechanical applications, this study established that: a ratio of fibres to a matrix of 4:1 is suitable for mechanical applications where all the flexural and tensile properties of the mono and hybrid composites are maximized. For applications that require the flexural properties of mono and hybrid nanocellulosic composites to be maximized, while the tensile properties of the mono and hybrid nanocellulosic composites are minimized, the ratio was found to be 1:2. A similar ratio was found to be suitable for applications that require the tensile properties of mono and hybrid nanocellulosic composites to be maximized while the flexural properties are minimized. For applications that required a target of 10 MPa for the tensile and flexural strength of mono and hybrid nanocellulosic composites and 10 GPa for the tensile and flexural stiffness of mono and hybrid nanocellulosic composites, this ratio was found to be 2:3.
D. Eng. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Abaqus software; Nanocellulosic fibres; Particle fillers; Finite Element Analysis; Natural fibres; Hybrid composites; Minitab software; Dissertations, Academic -- South Africa.; Cellulose fibers.; Polymers.; Polymeric composites.; Abaqus (Electronic resource).; Minitab.